2000
DOI: 10.1080/15257770008033048
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Drugs with DNA Gyrase: A Model for the Molecular Basis of Quinolone Action

Abstract: DNA gyrase supercoils DNA in bacteria. The fact that it is essential in all bacteria and absent from eukaryotes makes it an ideal drug target. We discuss the action of coumarin and quinolone drugs on gyrase. In the case of coumarins, the drugs are known to be competitive inhibitors of the gyrase ATPase reaction. From a combination of structural and biochemical studies, the molecular details of the gyrase-coumarin complex are well established. In the case of quinolones, the drugs are thought to act by stabilisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 62 publications
2
65
0
Order By: Relevance
“…This corresponds to the head dimer interface as shown by crystallization of the 59-kDa N-terminal domain of E. coli GyrA (30). The proposed region of interaction between MfpA Mt , QnrB4, and gyrase should thus include the QRDR domain of GyrA, in which residues S83 and D87 are strongly involved in the quinolone-gyrase interaction (4,16,48). We performed experiments with GyrA subunits modified at these two positions and found that the effect of MfpA Mt on gyrase catalysis was nearly abolished when the residue at position 87 in GyrA was changed, but not with substitutions at position 83.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This corresponds to the head dimer interface as shown by crystallization of the 59-kDa N-terminal domain of E. coli GyrA (30). The proposed region of interaction between MfpA Mt , QnrB4, and gyrase should thus include the QRDR domain of GyrA, in which residues S83 and D87 are strongly involved in the quinolone-gyrase interaction (4,16,48). We performed experiments with GyrA subunits modified at these two positions and found that the effect of MfpA Mt on gyrase catalysis was nearly abolished when the residue at position 87 in GyrA was changed, but not with substitutions at position 83.…”
Section: Discussionmentioning
confidence: 99%
“…Quinolones target type II topoisomerases, and their activity is measured by the inhibition of supercoiling by gyrase or decatenation by topoisomerase IV and stabilization of complexes composed of topoisomerase covalently linked to cleaved DNA (16). The DNA gyrase active enzyme is a GyrA 2 GyrB 2 heterotetramer.…”
Section: Stav][dn][lf][str][g]mentioning
confidence: 99%
“…Addition of the antibiotic norfloxacin induces lambdoid bacteriophages into the lytic life cycle (Matsushiro et al, 1999;Walterspiel et al, 1992) by activation of the RecAmediated SOS response (Heddle et al, 2000). RecA is then responsible for directing phage derepression via rapid autocleavage of the lambdoid repressor protein CI (Craig & Roberts, 1980).…”
Section: P C M Fogg and Othersmentioning
confidence: 99%
“…Quinolone drugs bind to gyrase-DNA complexes, but only weakly to either gyrase or DNA (34,37,38,41,47). It is thought that quinolones bind to a pocket consisting of the QRDR of GyrA and the region of distorted DNA bound to it (17). In such a pocket, the quinolone would interact with elements of both the DNA and the enzyme.…”
mentioning
confidence: 99%